Evaluasi Alokasi Anggaran Dana BOS untuk Gaji Guru Honorer Sekolah Dasar di Kabupaten Tasikmalaya - Hanifah, Hani; Hasanah, Hana Nur; Rahayu, Rina Nur; Nuraeni, Rani; Sianturi, Risbon; Nur, Lutfi (Jurnal PGSD, 2022)
In the state elementary school education unit in Tasikmalaya Regency, we find educators with civil servant status and honorary teachers. Civil Servant teachers are paid directly by the government, while honorary teachers are paid from funding sources that come from school operational funding provided by the government. The minister of education makes a policy so that honorary salaries are used at most 50% of the total allocation of school operational funding provided by the government. Knowing the following policies makes researchers interested in studying the evaluation of the budget allocation for school operational funding for the salaries of honorary teachers in the Tasikmalaya Regency. The research method was a descriptive qualitative method, by interviewing 55 honorary teachers spread over 55 public elementary schools in Tasikmalaya Regency. The results of this study indicate that honorary teachers have not received salaries in accordance with the policies made by the minister of education. Salaries are still met by the policy of the principal in each education unit and the amount of salary received by honorary teachers is still below the minimum wage standard for the Tasikmalaya Regency. So the government should pay attention to teacher salaries to achieve better education.